2016
DOI: 10.2220/biomedres.37.265
|View full text |Cite
|
Sign up to set email alerts
|

<b>Immunohistochemical localization of fatty acid transporters and MCT1 in the sebaceous glands of mouse </b><b>skin </b>

Abstract: The sebaceous glands secrete sebum to protect the epidermis and hairs by the oily products. The glands express several transporters and binding proteins for the production of fatty acids and uptake of their sources. The present immunohistochemical study examined the expression and localization of CD36, MCT1, FATP4, and E-FABP in the sebaceous glands, including the meibomian and preputial glands of mice. CD36 and MCT1 in sebaceous glands were largely co-localized along the plasma membrane of secretory cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Cluster of differentiation 36 (CD36) is a cell-surface glycoprotein consisting of 472 amino acid residues that is predicted to be anchored to the plasma membrane by two transmembrane domains located at positions 9–29 and 440–461 . CD36 is expressed in diverse cell types and plays multiple roles. For instance, it is well-known that CD36 expressed by macrophages substantially contributes to the capture and clearance of oxidized low-density lipoprotein (oxLDL) through the recognition of distinct species of oxidized glycerophosphatidylcholine (oxGPC), which can occur on the surface of the particles. , In addition, because of its expression in taste bud cells and its ability to recognize long-chain fatty acids (LCFAs), ,, CD36 has long been known to play an important role in the chemosensory detection of lipid species in the oral cavity. , Attempts have also been made to identify the site within the extracellular domain of CD36 (amino acids 30–439) that is critical for recognizing oxLDL/oxGPC and unsaturated LCFAs. Kar and co-workers have found that (i) a synthetic peptide comprising residues 154–168 of human CD36 strongly inhibits binding of oxLDL to the full-length receptor overexpressed in cultured mammalian cells and (ii) site-directed mutagenesis of Lys residues at positions 164 and 166 to glutamate almost abolishes binding of oxLDL to the receptor-expressing cells . Furthermore, we have shown that (i) a fluorescently labeled oxLDL (FL-oxLDL) specifically binds to synthetic peptides containing residues 154–168 of mouse CD36 immobilized onto solid supports and (ii) oxGPC species such as 1-palmitoyl-2-(5-keto-6-octenedioyl)­phosphatidylcholine (KOdiA-PC, one of the most potent lipid ligands of CD36 , ) inhibit the binding of FL-oxLDL to the peptides. These findings strongly suggest that the short region around residues 154–168 is necessary and sufficient for the binding of oxLDL/oxGPC.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster of differentiation 36 (CD36) is a cell-surface glycoprotein consisting of 472 amino acid residues that is predicted to be anchored to the plasma membrane by two transmembrane domains located at positions 9–29 and 440–461 . CD36 is expressed in diverse cell types and plays multiple roles. For instance, it is well-known that CD36 expressed by macrophages substantially contributes to the capture and clearance of oxidized low-density lipoprotein (oxLDL) through the recognition of distinct species of oxidized glycerophosphatidylcholine (oxGPC), which can occur on the surface of the particles. , In addition, because of its expression in taste bud cells and its ability to recognize long-chain fatty acids (LCFAs), ,, CD36 has long been known to play an important role in the chemosensory detection of lipid species in the oral cavity. , Attempts have also been made to identify the site within the extracellular domain of CD36 (amino acids 30–439) that is critical for recognizing oxLDL/oxGPC and unsaturated LCFAs. Kar and co-workers have found that (i) a synthetic peptide comprising residues 154–168 of human CD36 strongly inhibits binding of oxLDL to the full-length receptor overexpressed in cultured mammalian cells and (ii) site-directed mutagenesis of Lys residues at positions 164 and 166 to glutamate almost abolishes binding of oxLDL to the receptor-expressing cells . Furthermore, we have shown that (i) a fluorescently labeled oxLDL (FL-oxLDL) specifically binds to synthetic peptides containing residues 154–168 of mouse CD36 immobilized onto solid supports and (ii) oxGPC species such as 1-palmitoyl-2-(5-keto-6-octenedioyl)­phosphatidylcholine (KOdiA-PC, one of the most potent lipid ligands of CD36 , ) inhibit the binding of FL-oxLDL to the peptides. These findings strongly suggest that the short region around residues 154–168 is necessary and sufficient for the binding of oxLDL/oxGPC.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed in various cell types, in which it plays multiple roles (22,32). For instance, CD36 in macrophages contributes to the capture and clearance of oxidized forms of low-density lipoprotein (oxLDL) through the recognition of oxidized phospholipids (oxPLs) occurring on the surface of the particle (20,22).…”
Section: Introductionmentioning
confidence: 99%